Establishment of three new species of Rhabdoblatta Kirby, 1903 (Blattodea, Blaberidae, Epilamprinae) from China on the basis of molecular and morphological data - Guo, Lin; Zhang, Zhi-Yu; Cai, Jin-Zhuo; Wang, Zong-Qing; Che, Yan-Li (Zootaxa, 2024)
Combining the results of morphological identification and molecular species delimitation (ABGD), with newly sequenced 23 COI fragments from three new species and seven known species of Rhabdoblatta, we describe three species of Rhabdoblatta, namely Rhabdoblatta maculosa Guo et Che, sp. n., Rhabdoblatta equalisinensis Guo et Che, sp. n. and Rhabdoblatta cavicola Guo et Che, sp. n. Their morphological and the Rhabdoblatta maculosa Guo et Che, sp. n. habitat photographs are also included. There is also a checklist of Chinese Rhabdoblatta species.